PRE AND POST- MOULT EGG GEOMETRY DURING THREE DIFFERENT AGES IN FOUR VARIETIES OF INDIGENOUS ASEEL CHICKEN - Z. Ahmad; A.W. Sahota; M. Akram; A. Khalique; M. Shafique; S. Mehmood; M. Usman; G. Mustafa; M. S. Khan (Journal of Animal and Plant Sciences, 2014)
The effects of moulting and age on egg geometry were evaluated during three age groups in four varities of Aseel chicken. For this purpose, a total of 168 eggs from four varieties of Aseel hens (Mushki, Lakha, Mianwali and Peshawari), each having 3 age groups (young, 50-67 weeks; medium, 80 -97 weeks and old, 115-132 weeks) were collected during pre and post-moult phases. The data on egg geometry parameters thus collected during both the phases of the study were analyzed using analysis of variance technique through Randomized Complete Block Design. The results showed significantly higher egg breadth and egg shape index in post-moult phase than that of pre-moult, whereas, non-significant differences were observed in egg surface area, egg length and egg volume. Better values for egg length, egg volume and egg surface area were recorded in Lakha and Mushki, whereas, better egg shape index was observed in Mianwali and Peshawari varieties. Egg breadth was better in Lakha and Mianwali. Non-significant differences were observed in egg volume, egg surface area and egg shape index in different age groups. Egg length was significantly greater in older birds, while, egg breadth was the lowest in younger birds.
Keywords: Aseel chicken; Moulting; Shape Index; Surface Area; Egg Volume